A Rare Case of Babesia microti in San Francisco East Bay. (28th October 2020) - Abdelmonem, M; Yu, T; Scot, J; Bandak, R; Davis, V; Javaherchian, V; Hatten, G; Gines, M
Abstract: Introduction/Objective: Babesia microti, a zoonotic intraerythrocytic parasite, is the primary etiological agent of human Babesiosis in the United States. Human infections range from subclinical illness to severe disease resulting in death, with symptoms being related to host immune status. Despite advances in our understanding and management of B. microti, the incidence of infection in the United States has increased. Therefore, research focused on eradicating disease and optimizing clinical management is essential. Here we review this remarkable organism, with emphasis on the clinical, diagnostic, and therapeutic aspects of human disease. Methods: A 71-year-old Asian man presented to the emergency department in our San Francisco East Bay community hospital in July 2019 with complaints of high fever and chills for the last five days. The patient is a resident of Taiwan. He was visiting his daughter in New Jersey where he worked in her garden. He came to California to visit his son when he noted feelings of excessive tiredness, muscle aches, and headache. He also described a decrease in appetite and nausea with vomiting and diarrhea. Results: His chest x-ray showed increased diffuse bilateral pulmonary infiltrate. He has a history of coronary artery disease post stent placement in 2011 and history of benign prostatic hypertrophy post transurethral resection of the prostate (TURP) On physical exam, He was febrile (103.1°F) and scleral icterus was identified. Laboratory workup revealed findings suggestive of hemolysis including increased LDH (401 U/L) and increased unconjugated bilirubin (1.7 mg/dL), critically low platelets and white blood cells of (32 and 2.9), while hemoglobin & hematocrit values in the normal range (13. g/dL & 36.8%, respectively). Elevated liver enzymes were also noted; AST 72 U/L and ALT 59 U/L. Upon examination of the blood smear, Malaria -like organisms were detected, and Maltese cross forms were also visible in the red blood cells. Those findings were also seen using Giemsa stain and were confirmed at the Alameda county lab. PCR was also positive for Babesia microti. Investigation for concurrent infection with Ehrlichia chaffeensis, Anaplasma phagocytophilum and Borrelia burgdorferi was negative. Conclusion: This case highlights the importance of timely and effective collaboration between the laboratory staff and clinicians.